DC distribution network to enable integration of PV power sources, distributed energy storages and DC loads in future communities : part III - Zhang, Huan Huan (Nanyang Technological University, 2021)
With the rapid consumption of non-renewable energy resources, energy saving and storage is becoming more and more important. Researchers are focusing on the development of clean energy to replace conventional energy and to reduce carbon emissions. The most attractive clean energies are solar energies as well as battery storage system. They are widely used in commercial and residential buildings. This project addresses direct current (DC) distribution network to enable integration of solar Photovoltaic (PV) system, distributed energy storages and DC loads in future communities. It mainly focusses on the PV power sources, energy storage systems and DC compatible loads with inverters, electrical loads for a commercial building in Singapore. The aim of this project is to investigate all DC/DC converters, AC/DC converters and DC/AC converters used in both alternating current (AC) as well as DC distribution networks. Secondly, selecting various DC/DC converters used in AC as well as DC distribution networks. Lastly, calculating efficiency and cost of DC and AC distribution networks due to multiple conversions.